Evaluation of infestation and damage the larger grain borer (Prostephanus truncatus) (horn) (Coleoptera: bostrichidae) on selected food grain crops (2012)
The study evaluated the ability of the larger grain borer (LGB), Prostephanus truncatus (Horn) to infest and damage two varieties of sorghum (Sorghum bicolour), Sesame (Sesamum indicum) Cowpea (Vigna unguiculata) and maize (Zea mays). 100 g each of the grain products were infested with 5 pairs (5 males and 5 females) of 1-10 day old LGB for 90 days. At 90 days post-infestation of the crops, the insects and grain dust generated by the feeding activities of the insects were sieved out of the grains; the grains were separated into damaged and undamaged and data were taken on number of adult P. truncatus, number of larvae and pupae, number of larvae and pupae, number of adult mortality, weight of dust (g), weight of damaged grains (g), weight of undamaged grains (g) and final weight of grains (g). The results showed that all the 5 pairs of adult LGB introduced into the cowpea and sesame varieties died. Likewise, neither larvae nor pupae were found in the two grain products. The highest mean number of larvae and pupae (18.5) was recorded in the Suwan-1 maize variety, and it was significantly (P < 0.05) higher than the mean number found in the other grain products studied. The mean number of larvae (7.25) in Solo maize variety was significantly (P < 0.05) higher than the mean larvae number of 4.25 and 2.50 in Eyinfun and Ex-Minna sorghum varieties respectively. Significantly (P < 0.05) higher percentage grain damage (49.76) and percentage weight loss (12.89) were recorded in the Solo maize variety compared to percentage grain damage and percentage weight loss in other grain products. Likewise, the grain damage (23.06 %) and weight loss (8.04 %) in the Ex-Minna sorghum variety were significantly < 0.05) higher than percentage grain damage and percentage weight loss obtained in other grain products except Solo maize. A significantly (P < 0.05) lower grain damage (1.35 %) and grain weight loss (1.43 %) were obtained in the NICRIBEN and E8 sesame varieties respectively. The result of this study indicates the ability of LGB to bore and damage sorghum, maize, sesame and cowpea; with breeding restricted only to maize and sorghum. There were varietal differences in response of the grain products to LGB infestation and damage. Considering the importance of sorghum, maize, sesame and cowpea as a cheap source of carbohydrate and protein; concerted effort should be geared at controlling infestation of the grain products by LGB.